Layar Kecil, Masalah Besar: Analisis Penggunaan Smartphone dan Pengaruhnya terhadap Keterlambatan Berbicara Anak - Bachtiar, Yudi; Rayi Siti Fitriani (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
This research aims to analyze the relationship between smartphone use and speech delay in children. Over the past decade, the penetration of smartphones has increased significantly, resulting in early and intensive screen exposure among children. This study employs a quantitative method with structured surveys and direct observation of 10 children aged 4-5 years from diverse socioeconomic backgrounds. Data was collected regarding the daily duration of smartphone use, the type of content accessed, and parent-child interactions while using the device. Preliminary results indicate a significant negative correlation between the duration of smartphone use and the development of speech abilities. Children who spend more time with smartphones tend to show delays in reaching language development milestones compared to those with less exposure. Furthermore, this study identifies that the quality of parent-child interaction during smartphone use, such as joint discussions and verbal interactions, can mitigate and minimize the negative impact of smartphone usage. This research provides vital insights into the impact of digital technology on child development and offers recommendations for parents and early childhood education practitioners. Keywords: smartphone use, speech delay, child development, digital technology, parent-child interaction.